STUDI PENGARUH SOSIO DEMOGRAFI TERHADAP REMITTANCE PADA MIGRASI INTERNASIONAL TENAGA KERJA WANITA (TKW) DI KABUPATEN KERINCI PROVINSI JAMBI - ., Suandi (PIRAMIDA; Vol 15 No 2 (2019): PIRAMIDA`- Jurnal Kependudukan dan Pengembangan Sumber Daya Manusia, 2019)
The purpose of this study was to analyze the influence of socio demographics on Remittance of Women Workers (TKW) in Kerinci Regency, Jambi Province. The study design was croos-sectional. This research was conducted in Kerinci Regency by selecting four sub-districts, namely Danau Kerinci District, Keliling Danau, Bukit Kerman and Gunung Raya District. This research takes six calendar months. The object of research is the Female Workers (TKW) who work in Malaysia with marital status and have children. The research sample was taken by snaw ball sampling. The number of respondents was 64 people. Data were analyzed by descriptive and statistical tests using Multiple Linear Regression. The results showed that the number of remittances sent by TKW to families living in the original area really helped the needs of the family, reaching 58.42 percent. The results of the analysis showed that the factors of the number of family members, length of stay in the destination area, and family expenses in the area of ??origin had a significant effect on remittances, while the factors of age, level of education, and total income did not show a significant effect.